Gender Differences in Child Poverty and Social Exclusion Across Europe: A Comparative Focus on Serbia - Svetlana Vukosavljevic; Snezana Radovanovic; Olgica Mihaljevic; Nebojsa Zdravkovic; Vladislava Stojic; Stefan Milojevic; Jovana Radovanovic; Milos Stepovic; Katarina Janicijevic; Nevena Folic; Marija Radovanovic; Branka Markovic (Children)
Background: Child poverty is a critical issue that affects millions of children worldwide and represents a global issue. This article focuses on exploring the risk of child poverty and social exclusion across Europe, with Serbia being in a comparable position with respect to other countries with different levels of development. Methods: This is an epidemiological, retrospective, and descriptive study based on data on the national populations of the European countries within our research interest. The data analyzed in this study was taken from publicly available datasets from Eurostat. The indicators of interest were the ones considering the social inclusion of children in the time period between 2014 and 2023 for all European countries available in the datasets. Results: The indicator of the risk of poverty and social exclusion showed a decreasing trend in the majority of countries; but still, seven countries showed an increase during the observation period of one decade. The highest percentage was in Romania and the lowest in Slovenia. The indicator of the risk of poverty exhibited a significant difference in terms of gender (being mostly higher among females) in Bulgaria, Lithuania, Portugal, Sweden, Switzerland, Montenegro, Albania, and Turkey. The indicator of children living in households with very low work intensity exhibited a significant difference in terms of gender (being mostly higher among males) in Bulgaria, Lithuania, Malta, the Netherlands, Finland, Sweden, Switzerland, and Albania. The indicator of severe social and material deprivation exhibited a significant difference in terms of gender (being mostly higher among females) in Bulgaria, Denmark, Estonia, Lithuania, Montenegro, Albania, and Turkey. Serbia did not show a significant gender difference, but the male gender had higher values than the female for all indicators. Conclusions: Child poverty is a multifaceted issue that affects various aspects of children’s lives, including health, education, and social inclusion. Addressing this issue requires a comprehensive approach that includes social protection, access to quality services, and efforts to combat discrimination.